Health, Safety, and Environment in the Indonesian Film Industry - Imanjaya, Ekky; Pangabean, Cynthia MF (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: As stipulated in the Indonesian Labor Law, every worker is entitled to work safety and health protection, including the film industry. This research focuses on two articles in the Health, Safety, and Environment (HSE) regulations and the Law of Film Year 2009. However, the Indonesian film industry has not officially implemented these laws. There have been several cases of HSE, which caused death or fatal injuries to film workers, without applying the regulations. Other HSE issues include the cases where only a few film producers gave insurance to the film workers, applied proper risk assessment, or provided first aid kits. The paper will overview HSE in the Indonesian film industry by mapping out the problems and potential solutions. Methods: By having in-depth interviews with key persons in the field, such as the workers and film producers, this research aims to map out such issues and answering why and how the laws on work health and safety are not implemented in the Indonesian film industry. Result: This research has resulted in maps of problems and recommendations for policymakers, film workers, and related institutes concerning HSE and the rights of film workers, including of the lack awareness of film workers on HSE and HSE-related curriculum in film education, as well as the need for stronger film associations and union. Conclusion: HSE in the Indonesian film industry must be evaluated to be more effective. Some factors to be reviewed include law enforcement in contracts, health insurance, the collaboration of various parties, HSE-related knowledge in the curriculum in Indonesian film education, and the application of Work Competency Standards (SKKNI) to all film professional associations.